Метафоричний образ війни в українській пресі XX - початку XXI століття - Коротич, К.В. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2007)
Автор на материале украинской прессы XX - начала XXI ст. рассматривает различные типы метафор войны, а также факторы, послужившие причиной их возникновения. Анализирует некоторые механизмы возникновения идеологи-зированной языковой картины мира, создаваемой в прессе. The author considers the different types of the metaphors of the war as well as the reasons which have determined their appearance on the material of the Ukrainian press of the XX century and the beginning of the XXI century. Some mechanisms of an origination of created in a press ideological language picture of the world is analyzed.
Keywords: образ війни; українська преса; мовна картина світу; метафора